Advances in urology 2015–2016. (January 2017) - Brewster, Simon; Biers, Suzanne; Challacombe, Ben; Cresswell, Jo; Sinclair, Andrew; Smith, Daron
It has become customary that a session is held at the British Association of Urological Surgeons (BAUS) annual meeting wherein the most important advances in the major urological sub-specialities are summarised by British opinion leaders for the benefit of the core urologist. It gives us pleasure to present in this paper (to which the six authors contributed equally) the topics covered at the Liverpool BAUS meeting in June 2016.